Technical and Strategic Human Resources Management Effectiveness as Determinants of Firm Performance - Huselid, Mark A.; Jackson, Susan E.; Schüler, Randall S. (Academy of Management Journal, 1997)
We evaluated the impact of human resource (HR) managers' capabilities on HR management effectiveness and the latter's impact on corporate financial performance. For 293 U.S. firms, effectiveness was associated with capabilities and attributes of HR staff. We also found relationships between HR management effectiveness and productivity, cash flow, and market value. Findings were consistent across market and accounting measures of performance and with corrections for biases.